Novel bifunctional inhibitor of protease and α-amylase from Clitorea ternatea restricts the growth and development in Spodoptera frugiperda - Dongare, Pratiksha M.; Madage, Varsha A.; Deshpande, V. Neha; Joshi, Rakesh S.; Giri, Ashok P.; Pawar, Pankaj K. (International Journal of Biological Macromolecules, 2025)
An inhibitor molecule capable of inhibiting a wide range of digestive enzymes without affecting endogenous enzymes is always desirable. We report characterization of CteTAI (M.W. 14 kDa), a bifunctional inhibitor (BFI) protein from the seeds of Clitoria ternatea capable of inhibiting trypsin and alpha-amylase. It retains trypsin inhibition activity up to 60 degrees C and alpha-amylase inhibition up to 40 degrees C. Trypsin inhibition is stable across pH 1-12, while alpha-amylase inhibition is stable between pH 3-7. CteTAI is a noncompetitive inhibitor of trypsin and an uncompetitive inhibitor of alpha-amylase. It selectively inhibits proteases and alpha-amylases from various sources, without affecting alpha-amylase from human saliva and Bacillus spp. Proteomic analysis identified CteTAI as a bifunctional inhibitor exhibiting 41 % similarity to a bifunctional inhibitor from Sesbania bispinosa. Feeding Spodoptera frugiperda larvae with CteTAI-infused diet impaired energy metabolism, resulting in undernourished larvae and malformed adults incapable of flight and mating. Key nutritional indices (RGR, RCR, %ECI, %FDI) were severely reduced, indicating that CteTAI disrupts growth and development by inhibiting multiple protease and alpha-amylase isoforms. Biochemical characterization of newly identified CteTAI suggests its potential application in crop protection.
Keywords: alpha-Amylase inhibitors; Bifunctional inhibitor; Clitoria ternatea; Protease inhibitors; Spodoptera frugiperda